ANALISA BEBAN KERJA KARYAWAN PEMINDAHAN PAVING BLOCK - Bagus Rachman Saputra; Iftitah Ruwana; Sanny Andjar Sari (Jurnal Valtech, 2025)
PT ABC is a company that produces products in the form of paving blocks and precast. The workers in carrying out their duties found manual material handling activities from the printing place to the stock inventory place. In the absence of work facilities, it causes problems for workers, one of which is spinal disorders. This study aims to analyze the recommended workload through the calculation of recommended weight limit and lifting index. The results of manual calculations of two workers transferring paving blocks when starting the activity obtained a lifting index value of 4 to the destination of the final value of 5, so that immediate improvement is needed. Suggested improvements to reduce the level of musculoskeletal risk of moving paving blocks. The proposed improvement is to rearrange the production layout so that the distance of moving the paving block from the printing place to the stock inventory place becomes shorter